Reportage of artisanal mining and environmental issues in Zimbabwe by The Sunday News and The Standard from 2017 to 2018 - Rutope, John (Midlands State University, 2019)
The researcher explores the reportage of artisanal mining and environmental issues by The Sunday News and The Standard from 2017 to date. The research so to find out how the two newspapers frame, give prominence to news reports on artisanal mining and environmental issues in Zimbabwe. The research used the framing, ideology and political economy theories to find out how far these two newspapers give value to news on artisanal mining and environmental issues in Zimbabwe. The research was purely qualitative hence the researcher deployed qualitative research instruments, particularly archival research, interviews and questionnaires. The researcher extracted newspapers from the University library, special collections archive and used content analysis to analyse content of articles of the two newspapers relevant to the study. The researcher also interviewed editors and reporters of the two newspapers to find out how do they report on artisanal mining and environmental issues in Zimbabwe. 20 Questionnaires were as well administered to readers of the two newspapers specifically readers in Tynwald residential suburb in Harare. From the outcomes of the study the researcher found out that the two newspapers had contrasting ways of reporting artisanal mining in Zimbabwe and this has been directly influenced by political economy. On the other hand environmental issues were not well attended to by both newspapers.